Using Life Cycle Costing, Life Cycle Assessment, Social Life Cycle Assessment and Social Agricultural Metabolism for the sustainable management of Alentejo's olive grove systems - Hermeto Souza, Rachel (2022)
Sustainable management of agri-food systems is directly linked to the rational use of available natural resources and existing social and economic pressures. Sustainability assessment regarding the economic, social and environmental pillars can support decision-making processes, playing a role in the strategic and operational levels of planning and project processes, including policies, plans, programs, projects and activities or operations that address sustainable development goals and indicators (Ramos, 2019). In addition, understanding everything that surrounds this sustainability makes us have an understanding of the environmental, economic and social impacts of these activities, contributing to the management of natural and human systems. The application of appropriate sustainability assessment methodologies should be considered for taking measures to make those systems more sustainable, taking into account the operationalization of these methodologies by society (Ramos, 2019). In the case of agricultural and agri-food systems sustainability assessment is complex as it has to simultaneously satisfy economic viability, environmental protection and social equity, with the focus on the long term. Within these methodologies for assessing, measuring and monitoring impacts there are a set of tools linked to the life cycle methodology. According to De Luca et al., (2015a) life cycle methodologies are recognized as powerful tools that allow to assess the economic performance and estimate the social and environmental impacts of a product or service, also in contexts of agri-food production processes. They are useful tools to characterize and quantify various typologies of impact generated by all stages of a production process. In the evaluation of complex socio-environmental systems, such as agricultural and agri-food ones, uncertainty often arises and the quality of decision processes can be a major concern. Olive groves are an important crop for the Mediterranean region and the Alentejo region of Portugal. In the Portuguese context the Alentejo region seems to be undergoing a process of rapid agricultural intensification, despite its dry Mediterranean climate and a tradition of extensive, multi-functional agricultural systems. This has been fueled by local, national, European, and global factors and processes, in close alignment with the dynamics of urban-financial capitalism (Silveira et al., 2018). This intensification and its production practices alter environmental impacts and raise the question of the sustainability of these agricultural systems. Sustainable management of olive groves requires economic, social and environmental internalization to assess their production systems and processes. The general objective of this paper is to show the advantages of applying some of the Life Cycle Management (LCM) tools to analyze the sustainability of olive groves in the Alentejo region, Portugal. Specifically, following a methodological approach proposed in the international project Sustainolive (2021) referred in De Luca et al (2021), life cycle methodologies and agrarian social metabolism will be used to evaluate the economic, social and environmental performances of sustainable management systems in olive growing.